Peningkatan Pengetahuan dan Keterampilan melalui Penyuluhan dan Simulasi Bantuan Hidup Dasar pada Masyarakat Awam Pesisir di Dusun Kasuari Desa Asilulu Kecamatan Leihitu Kabupaten Maluku Tengah - Suardi Zurimi; Suratno Kaluku; Adolfina Bumbungan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The inability to deal with emergency patients is generally caused by failure to recognize risks, late referrals, lack of adequate facilities, and community knowledge and skills in recognizing high-risk situations. Counseling and training are important efforts to improve the knowledge and skills of ordinary people in providing prehospital help. The target output is to increase the knowledge and skills of the fishing community about Basic Life Assistance (BHD); able to know and understand and practice BHD. The implementation method is in the form of giving pre-test questionnaires, providing counseling, conducting post-tests, and BDH training/simulations. The results obtained showed that 30 participants were working as fishermen with all-male sex, participants were able to understand counseling materials about BHD, there was an increase in knowledge between before and after counseling, and participants were able to practice BHD correctly. The conclusion obtained is an increase in community knowledge and the ability to create independence to help by the competencies obtained from counseling and training.